Impresi Dukungan Sosial Teman Sebaya Terhadap Prilaku Agresivitas Mahasiswa PBA - Achmad Fauzan Dainuri; Septi Gumiandari (Universitas Palangka Raya, 2025)
Aggressiveness is a behavior characterized by behavior that aims to hurt or hurt others. This study aims to determine the influence of peer social support impressions on the aggressive behavior of students of the Arabic Language Education Study Program (PBA). This study uses a quantitative method with a survey research design. The research sample consisted of 30 PBA students who were randomly selected. Data were collected using a questionnaire instrument. Data analysis using multiple linear regression test The results showed that there was a significant relationship between the impression of peer social support and the aggressive behavior of PBA students. The higher the impression of peer social support felt by students, the lower their aggressive behavior. Based on the results of this study, it can be concluded that the impression of peer social support has an important role in reducing the aggressive behavior of PBA students. Therefore, it is important for PBA students to establish good relationships with their peers in order to get adequate social support.